A Plasmodium late liver stage arresting GAP provides superior protection in mice - Akancha Mishra; Plabita Paul; Mrigank Srivastava; Satish Mishra (npj Vaccines)
Abstract Liver-stage genetically attenuated malaria parasites (GAPs) are powerful immunogens that provide protection against sporozoite challenge. We previously generated two late liver-stage-arresting GAPs by deleting the stearoyl-CoA desaturase (Scd) or sporozoite conserved orthologous transcript 1 (Scot1) genes in Plasmodium berghei. Immunization with Scd or Scot1 GAP conferred complete protection against a sporozoite challenge. In a safety study, we observed rare breakthrough blood-stage infections in mice inoculated with high doses of sporozoites, indicating that both GAPs were incompletely attenuated. In this study, we generated a Scd/Scot1 GAP by dual gene deletion. This resulted in complete attenuation of the parasites in the liver and did not transition to blood-stage infection despite a high-dose sporozoite challenge. The Scd/Scot1 KO and WT GFP parasites were indistinguishable during blood, mosquito and early liver stage development. Moreover, Scd/Scot1 KO liver-stage schizonts exhibited an abnormal apicoplast biogenesis and nuclear division phenotype, failed to form hepatic merozoites, and exhibited late liver-stage arrest. Compared with early-arresting Speld KO immunization, late-stage liver-arresting Scd/Scot1 KO induces greater and broader CD8+ T-cell responses and elicits stage-transcending immunity that provides superior protection in C57BL/6 mice. These data prove that multiple gene deletions lead to complete attenuation of the parasite and support the development of late liver stage-arresting P. falciparum GAP.